S.O.R. losers - Avi, 1937- (New York : Simon & Schuster Books for Young Readers, 1984)
Each member of the South Orange River seventh-grade soccer team has qualities of excellence, but not on the soccer field.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.0
4-6
5-8
Keywords: Soccer -- Fiction; Sports -- Fiction; Soccer -- Fiction; Sports -- Fiction